2005
DOI: 10.1038/sj.emboj.7600791
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 interaction with nuclear corepressor KAP1 contributes to p53 inactivation

Abstract: MDM2 is a RING domain ubiquitin E3 ligase and a major regulator of the p53 tumor suppressor. MDM2 binds to p53, inactivates p53 transcription function, inhibits p53 acetylation, and promotes p53 degradation. Here, we present evidence that MDM2 interacts with the nuclear corepressor KAP1. The binding is mediated by the N-terminal coiled-coil domain of KAP1 and the central acidic domain of MDM2. KAP1 stimulates formation of p53-HDAC1 complex and inhibits p53 acetylation by interacting with MDM2. Expression of KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(228 citation statements)
references
References 44 publications
5
221
0
2
Order By: Relevance
“…Nuclei were pelleted, lysed in Triton X-100 buffer 46 and used for detection of transfected proteins by western blotting. Lentiviral vector-based KAP1 gene knockdown was performed as described previously 47 .…”
Section: Gene Repression Assaymentioning
confidence: 99%
“…Nuclei were pelleted, lysed in Triton X-100 buffer 46 and used for detection of transfected proteins by western blotting. Lentiviral vector-based KAP1 gene knockdown was performed as described previously 47 .…”
Section: Gene Repression Assaymentioning
confidence: 99%
“…19 Fifth, MDM2 may also contribute to p53 inactivation by recruiting several corepressor proteins, such as HDAC1, 20 CTBP2, 21 YY1, 22 and KAP1. 23 A central negative regulator of MDM2 is the tumor suppressor protein p14 ARF , which is an alternate reading frame product of the CDKN2A locus on chromosome 9p21. This locus encodes two structurally unrelated growth-inhibitory proteins, p16 INK4a and p14 ARF , that govern the activities of the pRb and p53 tumor suppressor pathways, respectively.…”
mentioning
confidence: 99%
“…Furthermore, this enhancement relied on the interaction between the two proteins, since the MAGE-G1 L96A/L97A mutant lost the enhancement effect. In the case of MAGE-C2-TRIM28 complex, MAGE-C2 could not only induce the ubiquitin ligase activity of TRIM28 itself, but also enhance the ubiquitination of its substrate p53 by TRIM28 (Wang et al, 2005;Doyle et al, 2010). In addition, Yang et al (2007) also showed that type I MAGEs binding to TRIM28 suppressed p53-dependent apoptosis in cancer cells.…”
Section: Function and Mechanism Of Mage-ring Complexesmentioning
confidence: 94%